Spectrum of elastin sequence variants and cardiovascular phenotypes in 49 patients with Williams–Beuren syndrome1. Issue 3 (7th February 2013) - Delio, Maria; Pope, Kathleen; Wang, Tao; Samanich, Joy; Haldeman‐Englert, Chad R.; Kaplan, Paige; Shaikh, Tamim H.; Cai, Jinlu; Marion, Robert W.; Morrow, Bernice E.; Babcock, Melanie
Abstract Haploinsufficiency of the elastin gene (ELN) on 7q11.23 is responsible for supravalvular aortic stenosis (SVAS) and other arteriopathies in patients with Williams–Beuren syndrome (WBS). These defects occur with variable penetrance and expressivity, but the basis of this is unknown. To determine whether DNA variations in ELN could serve as genetic modifiers, we sequenced the 33 exons and immediately surrounding sequence of the ELN gene (9, 455 bp of sequence) in 49 DNAs from patients with WBS and compared cardiovascular phenotypes. Four missense, and four novel intronic variants were identified from a total of 24 mostly intronic single nucleotide variations and one indel. Two missense changes were present in one patient each, one published, p.Gly610Ser in exon 27 (MAF, 0.003) and one novel, p.Cys714Tyr, in exon 33 (MAF, 0.001), were rare in the general population. To identify a statistical association between the variants identified here and cardiovascular phenotypes a larger cohort would be needed. © 2013 Wiley Periodicals, Inc.